Name of Musical Instruments in Russian and Uzbek Languages - Akabirova G.S. (European Science Publishing, 2023)
The name of the group "Musical Instruments" in modern Russian is analyzed. The results of the lexico-semantic analysis of these lexemes are given, which showed the presence of homonyms, but the complete absence of synonyms, antonyms, paronyms. Hyperonymic-hyponymic relations are considered, the prevalence of borrowed words and terms is fixed.